Current Topics in Children's Learning and Cognition - Kloos, Heidi; Morris, Bradley J.; Amaral, Joseph L. (IntechOpen, 2012)
As a whole, the essays in this book address theoretical and empirical issues related to children's learning and cognition. The first essay, titled Learning in Cognitive Niches, treats the process of sense making on a theoretical level, discussing the complexity of factors that give rise to children's learning. It is followed by an essay, titled Using the Dynamics of a Person-Context System to Describe Children's Understanding of Air Pressure, that applies ideas from complexity science and dynamics-systems theory to children's learning about science. The next four essays summarize and synthesize already published findings, in an effort to go beyond individual viewpoints and present a more nuanced picture of children's sense making. In particular, two of these summaries, Preschoolers Learning Science: Myth or Reality? and The Emergence of Scientific Reasoning, focus on children's ability to make sense of their physical environment. The essay Cognition and the Child Witness: Understanding the Impact of Cognitive Development in Forensic Contexts seeks to shed light on children's sense making relevant to forensic issues. And the essay Beyond the Black-and-White of Autism: How Cognitive Performance Varies with Context ventures in the area of autism, a disorder that demonstrates atypical processes of combining pieces of information. The final two essays provide original data to add to the discussion of what factors affect cognitive functioning. In particular, the essay Cognitive Fitness in Young Adult Video Game Players seeks to re-assess the often-assumed relation between video gaming and various aspects of thinking, memory, intelligence, and visual-spatial abilities. And the essay Impact of Moving Away from Home on Undergraduate Metacognitive Development explicitly connects life circumstances to the ability to monitor and control one's thinking. Together, the collection of essays are a further step towards understanding the process of sense making as children and young adults interact with their environment.